3-D travel-time tomography of southernmost Baja California Peninsula. (January 2021) - Huesca-Pérez, Eduardo; Gutierrez-Reyes, Edahí; Valenzuela, Raúl W.; Husker, Allen; Mayer, Sergio
Abstract: A three-dimensional P and S-wave travel-time tomography, as well as Vp/Vs ratio images, were obtained for the southernmost tip of the Baja California Peninsula in Mexico. The area analyzed include Los Cabos block and part of the Gulf coast. The tomography obtained reveals in detail the heterogeneities of the crustal seismic velocity structure of the Los Cabos block. Results show an overall low velocity structure for both P- and S-waves under the Baja California peninsula down to a depth of ~25 km around the peninsular axis, particularly under Sierra La Laguna and near the Gulf of California (GoC) coast. Low P- and S-wave velocities are also present under the Gulf near the coast whereas fast velocities are observed under the Gulf away from the shoreline. Low and high Vp/Vs ratios are observed to alternate throughout the study area. The low seismic velocities may be explained because the crust in Los Cabos block is highly fractured and fluid-saturated, and has a high heat flux which is manifested as geothermal activity (e.g. hot springs observed all along the block). These low body wave velocities coincide with the existence of an asthenospheric mantle sandwiched by the continental crust of the Los Cabos block and a stalled subducted slab reported by Di Luccio et al. (2014). This mantle strip may be chemically depleted or dry inhibiting the development of active post-subduction volcanism.